2021
DOI: 10.1038/s41598-021-85450-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with resolution of type-2 diabetes mellitus after sleeve gastrectomy in obese adults

Abstract: Many bariatric procedures are more effective for improving type-2 diabetes mellitus (T2DM) than conventional pharmacotherapy. The current research evaluated factors linked to complete and partial remission or improvement of T2DM after laparoscopic sleeve gastrectomy (LSG). The current prospective study included all diabetic patients who were submitted LSG between January 2015 and June 2018 and completed a 2-year follow-up period. Patients were assessed at baseline and 2 years after LSG. This work comprised of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 63 publications
(74 reference statements)
0
7
0
2
Order By: Relevance
“…Bariatric surgery offers an efficient approach for managing obesity, with various surgical procedures available [34]. Among these, sleeve gastrectomy accounts for 55.4% of all bariatric surgeries thanks to its minimal invasiveness [35] and has been shown to resolve IR and T2D [36]. In our study, one year after sleeve gastrectomy, all patients exhibited a HOMA-IR below 2.5 and a two-fold increase in adiponectin concentration.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Bariatric surgery offers an efficient approach for managing obesity, with various surgical procedures available [34]. Among these, sleeve gastrectomy accounts for 55.4% of all bariatric surgeries thanks to its minimal invasiveness [35] and has been shown to resolve IR and T2D [36]. In our study, one year after sleeve gastrectomy, all patients exhibited a HOMA-IR below 2.5 and a two-fold increase in adiponectin concentration.…”
Section: Discussionmentioning
confidence: 61%
“…[41]Among all types of surgery, sleeve gastrectomy is currently the most frequently performed procedure in the world, accounting for 55.4% of all bariatric surgeries [42], and remains the most favorable strategy due to its relative simplicity, minimal invasiveness, and efficiency in terms of weight loss [42, 43]. Sleeve gastrectomy also impairs insulin resistance and improves diabetes [44]. In our study, one year after sleeve gastrectomy, all patients exhibited a HOMA-IR below 2.5 and a two-fold increase in the adiponectin concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study included the rate of weight loss throughout the 1year follow-up, the amelioration of comorbidities, improvement of the QoL, operative time, hospital stay, any intraoperative mishaps e.g., bleeding, organ injury, conversion, and the cause of conversion if occurred, and postoperative complications. Concerning the amelioration of comorbid diseases, the resolution of type II diabetes mellitus depended on HbA1c < 6% or fasting blood glucose less than 100 mg/dl in the absence of hypoglycemic drugs [18]. The complete resolution of hypertension was based on blood pressure less than 120/80 without using medications, while its improvement was considered a reduction in dosage or number of anti-hypertensive drugs or systolic and diastolic pressure with the similar drugs [19].…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study comprising 226 T2DM patients with a BMI of > 35 showed a rate of 38.1%, and 10.6% complete and partial remission of T2DM after LSG, respectively, at two years follow-up. On logistic regression, an age of < 45 years, and a short duration of T2DM from diagnosis were found to be independent predictors of complete remission [ 23 ]. A retrospective analysis of 143 obese patients diagnosed with hypertension who underwent LSG showed 23% and 63% complete and partial remissions of hypertension, respectively, at 12 months [ 24 ].…”
Section: Discussionmentioning
confidence: 99%